Treatment of Extensive Eyelid Molluscum Contagiosum with Physical Expression Alone in an Immunocompetent Child - Gamze Öztürk Karabulut; Can Öztürker; Pelin Kaynak; Serpil Akar; Ahmet Demirok (Türk Oftalmoloji Dergisi, 2014)
Molluscum contagiosum is a common viral skin infection in children with dome-shaped umbilicated nodules. Diagnosis is based on clinical appearance. An eight-year-old child presented to our clinic with multiple molluscum contagiosum nodules on the right lower and upper eyelid and one small papule on the left upper eyelid. Only a couple of lesions were squeezed with expression of cheesy material from the center of the lesions. In the follow-up period, beside resolution of the squeezed lesions, all other lesions disappeared spontaneously and no new lesion was observed in the following one year. This method is costless, neither needs a chemical agent nor results in scarring, so can be the first choice of treatment. (Turk J Ophthalmol 2014; 44:158-60)